2021
DOI: 10.1002/cplu.202100137
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Recognition of Aromatic Species with Ferrocenylated 1,3,5‐Triazine‐ or 1,3,5‐Triphenylbenzene‐Containing Highly Organized Molecules

Abstract: Two ferrocenylated organized molecules comprising 1,3,5triphenylbenzene (Fc-1) or 2,4,6-triphenyl-1,3,5-triazine skeletons (Fc-2) were used for the first time as receptor layers for the electrochemical recognition of polycyclic aromatic hydrocarbons. While our group recently reported the synthesis of Fc-1, herein the facile synthesis of its 2,4,6-triphenyl-1,3,5-triazinecontaining structural analog (Fc-2) is presented. Although the synthesis of Fc-2 was found to be challenging, we achieved a very high yield (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Therefore, we tried to synthesise the known Tri 2 Di 3 cage FcC4 , by using two equivalents of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine ( 7 ) and three equivalents of 1 . 20 We were ultimately able to synthesise FcC4 in 40% yield, after ball-milling the starting materials for 3 h at 25 Hz (Fig. 4c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, we tried to synthesise the known Tri 2 Di 3 cage FcC4 , by using two equivalents of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine ( 7 ) and three equivalents of 1 . 20 We were ultimately able to synthesise FcC4 in 40% yield, after ball-milling the starting materials for 3 h at 25 Hz (Fig. 4c).…”
Section: Resultsmentioning
confidence: 96%
“…Only two cage compounds using 1 as a building block have been reported in the literature to this date. 16 e ,20 In both cases, the formyl groups are found to be stacked above one another ( syn conformation), minimizing the distance between the two triamines that form the top and bottom parts of these small triangular prims. In the crystal structure of FcC1 , the Cp-units are rotated 150° against each other ( anti conformation).…”
Section: Resultsmentioning
confidence: 99%
“…Changing the temperature to 85°C also did not result in the formation of FcB-cage and once again starting materials were recovered only. Attempts to synthesize FcB-cage by applying the reported procedures for the synthesis of other ferrocene containing organic cages, which employed methanol or ethanol as the solvent, 28,29 were also unsuccessful (recovery of starting materials). We suspected that the difficulties in dissolving 1,1ʹ-ferrocenediboronic acid 1 or HHTP could be the culprit behind those above-discussed unsatisfactory results.…”
Section: Synthesis Of Fcb-cagementioning
confidence: 99%
“…Recently, it has been demonstrated that organic cages derived from the 1,1ʹ-diformylferrocene can be easily and effectively synthesized by means of the imine bond formation reaction with C3-symmetric aromatic amines. 28,29 Such an organic cage can be viewed as two parallel 2D sheets connected via a linkage that is perpendicular to those sheets. More specifically, the two parallel 2D sheets are rigid aromatic frameworks, while the three linkages are the ferrocene units.…”
Section: Introductionmentioning
confidence: 99%